Implementasi Pendekatan Kontekstual dalam Pembelajaran Pendidikan Agama Islam pada Peserta Didik di MTs Muhammadiyah Datarang Kabupaten Gowa - Ferdinan Ferdinan (Departement of Mathematics Education, 2023)
This research demonstrates that: 1. Teacher planning in Islamic Religious Education with a contextual approach for students at MTs Muhammadiyah Datarang, Gowa Regency, involves teachers preparing and developing Lesson Planning Programs (RPP) in accordance with the conceptual learning concepts related to Constructivism, Inquiry, Group Learning, Questioning, and Modeling. All of these elements are aligned with the objectives of each competency standard. 2. The Implementation of the Contextual Approach in Teaching Islamic Religious Education to Students at Mts Muhammadiyah Datarang involves Islamic Religious Education teachers conducting lessons with a conceptual approach. This implementation is related to: a) the constructivist approach that emphasizes giving students the opportunity to learn independently and discover and apply their own ideas related to the topics provided by the teacher, b) inquiry that emphasizes students' ability to discover and identify problems raised through various sources or relevant reference books related to the subject matter, c) group learning that emphasizes collaborative learning activities among students by discussing various topics determined by the Islamic Religious Education teacher and then being accountable by presenting them in front of the class, d) questioning, where students are encouraged to ask questions so that they can get answers from the teacher for what they do not understand, and likewise, the teacher always asks students questions to ensure that students have the ability to master the subject matter provided, e) modeling, where students learn by demonstrating short dramas based on what the teacher has provided to facilitate a better understanding of each topic related to Islamic Religious Education material.